A novel frameshift variant in the MED13 gene causing intellectual developmental disorder-61 in a Chinese family - Yang, Qi; Zhang, Qiang; Yi, Sheng; Huang, Gaojie; Zhou, Xunzhao; Yi, Shang; Luo, Jingsi (Frontiers in Pediatrics, 2025)
Intellectual developmental disorder type 61 (MRD61) is an extremely rare autosomal dominant disorder caused by variants in the MED13 gene. This gene encodes a subunit of the mediator complex, which is also known as TRAP, SMCC, DRIP or ARC. This complex functions as a transcriptional coactivator and is essential for the expression of almost all genes. To date, only 26 cases of MRD61 have been reported worldwide. The main symptoms are intellectual disability (ID) of varying degrees, developmental delay (DD), hypotonia during infancy, facial dysmorphism, language impairment, restricted growth, skeletal and limb abnormalities, and behavioral abnormalities. In this study, we recruited a Chinese family in which two individuals were diagnosed with MRD61. Whole-exome sequencing of the proband revealed a novel heterozygous frameshift variant in the MED13 gene (NM_005121.3): c.5641delinsTC (p.R1882Sfs*9). This variant was inherited from the affected mother and was subsequently confirmed in both the proband and her other family members using Sanger sequencing. The dysmorphology profile of both patients described here is similar to that associated with MRD61. Compared with previously reported cases of MRD61, the proband presented with congenital megacolon, a previously unreported complication. Additionally, skeletal and limb deformities, eye or vision abnormalities, behavioral issues and brain abnormalities were absent in our patients. This is the first report of MED13-associated intellectual developmental disorder-61 in China. This molecular diagnosis expands the known genetic spectrum of MRD61. Furthermore, the specific manifestations observed in these patients with this condition provide valuable additional clinical insight into the syndrome.